2007
DOI: 10.2337/dc06-1735
|View full text |Cite
|
Sign up to set email alerts
|

Fasting Glucose in Acute Myocardial Infarction

Abstract: OBJECTIVE -Elevation of blood glucose is a common metabolic disorder among patients with acute myocardial infarction (AMI) and is associated with adverse prognosis. However, few data are available concerning the long-term prognostic value of elevated fasting glucose during the acute phase of infarction.RESEARCH DESIGN AND METHODS -We prospectively studied the relationship between fasting glucose and long-term mortality in patients with AMI. Fasting glucose was determined after an Ն8 h fast within 24 h of admis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
31
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 43 publications
(37 reference statements)
3
31
0
1
Order By: Relevance
“…Many prior studies have observed that the nature of the relationship between initial glucose levels and short-term mortality differs between patients with and without diabetes. 2,15,21,29,30,32 The risk of mortality rises gradually once glucose levels exceed ~110-120 mg/dL (6.1-6.6 mmol/L) in patients without diabetes, whereas in patients with established diabetes the risk does not increase substantially until glucose levels exceed ~200 mg/dL (11.0 mmol/L). 2,29 Thus, different definitions of hyperglycaemia may be appropriate according to whether established diabetes is present.…”
Section: Hyperglycaemia Definitionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many prior studies have observed that the nature of the relationship between initial glucose levels and short-term mortality differs between patients with and without diabetes. 2,15,21,29,30,32 The risk of mortality rises gradually once glucose levels exceed ~110-120 mg/dL (6.1-6.6 mmol/L) in patients without diabetes, whereas in patients with established diabetes the risk does not increase substantially until glucose levels exceed ~200 mg/dL (11.0 mmol/L). 2,29 Thus, different definitions of hyperglycaemia may be appropriate according to whether established diabetes is present.…”
Section: Hyperglycaemia Definitionmentioning
confidence: 99%
“…25,32,35,36 Unlike the random glucose level on admission, elevated fasting glucose may be a better reflection of abnormalities in underlying glucose metabolism, and thus may be a better predictor both of short-term and long-term outcomes. In one of the earlier studies on this issue, Suleiman et al demonstrated that while both admission and fasting glucose levels predicted 30-day mortality in non-diabetic patients with AMI, fasting glucose was the better discriminator.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These findings were comparable to the previously reported clinical trials. [12][13][14][15][16] In five large, randomized trials [17][18][19][20][21] [Veterans Affairs Non-Q-Wave Infarction Strategies in Hospital (VANQ-WISH), Fragmin and Fast Revascularization during Instability in Coronary Artery Disease (FRISC) II, Treat Angina with Aggrastat and Determine the Cost of Therapy with an Invasive or Conservative Strategy-Thrombolysis in Myocardial Infarction 18 (TACTICS-TIMI 18), TIMI IIIB and the Third Randomized Intervention Treatment of Angina (RITA-3)], a routine, early invasive strategy (early angiography followed by revascularization, depending on the angiographic findings) was compared with a "conservative" strategy (angiography and subsequent revascularization only if medical therapy failed or substantial residual ischemia was documented). An early invasive strategy was shown to be beneficial by the FRISC II, TACTICS-TIMI 18 and RITA-3 studies, and especially for the subgroups of patients who were at a high risk, such as those patients presenting with an elevated cardiac troponin level.…”
Section: Discussionmentioning
confidence: 99%
“…More recent publications have shown the clinical relevance of fasting glucose level in ACS [19][20][21][22][23][24][25][26][27] . Studies that assessed adequately fasting plasma glucose (FPG) levels in acute myocardial infarction (AMI) patients show that it is a predictor for complications after AMI, and may even be better than admission FPG to predict in-hospital and short-term mortality 19,25,27 . Another study has also shown that FPG was a good predictor of long-term mortality in non-diabetic AMI patients…”
mentioning
confidence: 99%